Exercício contínuo e intermitente: Efeitos do treinamento e do destreinamento sobre a gordura corporal de ratos obesos - Braga, Larissa Ribeiro [UNESP]; De Mello, Maria Alice Rostom [UNESP]; Gobatto, Claudio Alexandre [UNESP] (My University, 2004)
Exercise training is often recommended in prevention and treatment of obesity. The present study was designed to compare the effects of intermittent and continuous exercise on weight loss and carcass composition in obese rats. Obese male Wistar rats (monosodium glutamate [MSG] administration, 4 mg/g of body weight every other day from birth to 14 days old) were used. After drug administration, the rats were separated into three groups: MSG-SED (sedentary), MSG-CONT (continuous, swimming, 45 min/day, 5 days/week, with and overload of 5% body weight for 12 weeks) and MSG-INT (intermittent, 15s swimming intermitted by 15s rest, during 45 min, 5 days/week, with and overload of 15% body weight for 12 weeks). Rats of the same age and strain, administered with saline were used as control (SAL), and subdivided into three groups: SAL-SED, SAL-CONT and SAL-INT. The animals were evaluated at the 10 weeks of training and 8 weeks of its interruption. MSG rats showed higher carcass fat as well as weight and cell size in epididymal adipose tissue than SAL rats, indicting the efficacy of the drug in producing obesity. Intermittent training protocol led to a reduction in blood lactate accumulation during acute exercise and both protocols reduced body weight gain during the experiment in MSG rats. After 8 weeks of training interruption no differences were observed among groups in the examined parameters. Only intermittent exercise training improved aerobic fitness but both protocols were similarly efficient in determining weight loss. However, the effects were transitory, since they disappeared after detraining.
Continuous and intermittent exercise: Effects of training and detraining on body fat in obese rats
Keywords: Continuous exercise and weight loss; Exercise; Intermittent exercise; Obesity; adipose tissue; animal experiment; animal model; body weight; controlled study; evaluation; exercise; lactate blood level; male; nonhuman; obesity; rat; sitting; swimming; training; weight gain; weight reduction; Adipose Tissue; Animals; Animals, Newborn; Lactic Acid; Male; Physical Conditioning, Animal; Rats; Rats, Wistar; Sodium Glutamate; Time Factors; Weight Gain; Animalia; Rattus norvegicus